Phylogeny of Cassieae based on seed morphological and ITS evidence - Cai, Jing; Yang, Chuang; Wang, Leyang; He, Jiaqing; Wang, Qiang (PeerJ, 2025)
The Cassieae tribe, comprising economically significant species, is understudied in terms of phylogenetics within China. This study aimed to elucidate the taxonomic status and systematic relationships among Cassieae species by integrating seed coat micro-morphological characteristics with molecular data from the internal transcribed spacer (ITS) region of nuclear ribosomal DNA. (1) The results indicate that the tribe is classified into seven distinct clades; Clade V consists of Chamaecrista, which is characterized by primarily monosymmetric flowers with occasional asymmetry, the presence of extrafloral nectaries (EFNs), five or ten stamens, and pods that dehisce elastically. Clade VI is associated with Senna, which displays polysymmetric or monosymmetric flowers, uniformly ten stamens or occasionally three staminodes, variable presence of EFNs, and predominantly indehiscent pods, with rare instances of slit dehiscence. Clade VII is characterized by the presence of Cassia, which exhibits polysymmetric flowers, consistently ten stamens—three of which are elongated and curved, typically exceeding the length of the petals—and indehiscent pods. (2) The monophyly of Cassia and Senna was strongly supported, with Cassia grouping closely with Senna, but distantly from Chamaecrista. (3) It is noteworthy that Senna occidentail and Senna sophera are confirmed as sister taxa, while Senna corymbosa and S. bicapsularis are confirmed as sister taxa. By integrating molecular biology and morphological taxonomy, this research enhances our comprehension of the phylogenetic relationships and evolutionary history within the Cassieae tribe in China.
Keywords: Cassiinae; EFNs; Seed coat micro-morphology; ITS region; Phylogeny